E-MODULE DEVELOPMENT ON RIGHTS AND OBLIGATIONS LEARNING MATERIALS TO INCREASE STUDENTS’ UNDERSTANDING AT GRADE III - Alsha Noer Oktaviani Ibrahim; Isrok'atun Isrok'atun; Rana Gustian Nugraha (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the process of e-module development on the learning material of rights and obligations to increase the understanding of class III students. The research described in this paper is developmental research (Design and Development) with the ADDIE model, which consists of five stages, Analyze, Design, Development, Implementation, and Evaluation. The validation of development products is tested through 1 media/design expert, 1 material expert, and 1 linguist. The data collection instruments in the research use validation sheets and pretest and posttest questions. E-module development on the right and obligation to increase understanding of class III students meets excellent criteria with an average percentage of validity at 91.37%. After testing the effectiveness through data processing of pretest and posttest value results, it was found that there has been an increased understanding of class III students after applying the learning media of the e-modules that have been developed. It is also indicated by the difference between the average value of the pretest and posttest results, where the value of the posttest is an average of 94.33 higher than the value the pretest by an average of 80,33. The implementation in this paper is recommended for further researchers in order to be able to develop learning media like e-modules by applying a particular learning method or a more interesting and creative application. In addition, it is also required further research validation will be applied more than once and the effectiveness tests are made on more subjects.